Gene expression profile indicates involvement of NO in Camellia sinensis pollen tube growth at low temperature. (December 2016) - Pan, Junting; Wang, Weidong; Li, Dongqin; Shu, Zaifa; Ye, Xiaoli; Chang, Pinpin; Wang, Yuhua
Abstract Background Nitric oxide (NO) functions as a critical signaling molecule in the low-temperature stress responses in plants, including polarized pollen tube growth inCamellia sinensis . Despite this, the potential mechanisms underlying the participation of NO in pollen tube responses to low temperature remain unclear. Here, we investigate alterations to gene expression inC. sinensis pollen tubes exposed to low-temperature stress and NO using RNA-Seq technology, in order to find the potential candidate genes related to the regulation of pollen tube elongation by NO under low-temperature stress. Results Three libraries were generated fromC. sinensis cv. 'Longjingchangye' pollen tubes cultured at 25 °C (CsPT-CK) and 4 °C (CsPT-LT) or with 25 μM DEA NONOate (CsPT-NO). The number of unigenes found for the three biological replications were 39, 726, 40, 440 and 41, 626 for CsPT-CK; 36, 993, 39, 070 and 39, 439 for CsPT-LT; and 39, 514, 38, 298 and 39, 061 for CsPT-NO. A total of 36, 097 unique assembled and annotated sequences fromC. sinensis pollen tube reads were found in a BLAST search of the following databases: NCBI non-redundant nucleotide, Swiss-prot protein, Kyoto Encyclopedia of Genes and Genomes, Cluster of Orthologous Groups of proteins, and Gene Ontology. The absolute values of log2 Ratio > 1 and probability > 0.7 were used as the thresholds for significantly differential gene expression, and 766, 497 and 929 differentially expressed genes (DEGs) were found from the comparison analyses of the CK-VS-LT, CK-VS-NO and LT-VS-NO libraries, respectively. Genes related to metabolism and signaling pathways of plant hormones, transcription factors (TFs), vesicle polarized trafficking, cell wall biosynthesis, the ubiquitination machinery of the ubiquitin system and species-specific secondary metabolite pathways were mainly observed in the CK-VS-LT and CK-VS-NO libraries. Conclusion Differentially expressed unigenes related to the inhibition ofC. sinensis pollen tube growth under low temperature and NO are identified in this study. The transcriptomic gene expression profiles present a valuable genomic tool to improve studying the molecular mechanisms underlying low-temperature tolerance in pollen tube.